Interaktivitas Website di Biro Humas dan Protokol Pemerintah Provinsi Kepulauan Bangka Belitung - Peni Oktariana; Nathalia Perdhani (Fakultas Ilmu Komunikasi Universitas Pancasila, 2016)
This study discusses how website interactivity owned by Provincial Government of Bangka Belitung Islands which is managed by Bureau of Public Relations and Protocol. The method used in this research is qualitative descriptive with post-positivism paradigm. The concept used is Public Relations 2.0 and Interactivity Website. There are six important components in a website to be said interactive, namely user control, responsiveness, real time interactions, connectedness, personalization/ customization, and playfulness. The results of this study indicate that public relations at the Bureau of Public Relations and Protocol has started to integrate with the website. This is indicated by the presence of staff who can answer public questions, updated information daily, and start adding video features that are expected to make repeat visits. However, this study found that on the Website of Public Relations and Protocol Bureau of the Provincial Government of Bangka Belitung Islands there is only one component of the six important components of the website, namely user control, and from one component there is only a feature of time only. Features of freedom of choice of language, freedom of choice of text type, and search engine which also exist in user control component not yet exist on website. It shows that there is no interactivity on Website Bureau of Public Relations and Protocol of Provincial Government of Bangka Belitung Islands.